Etiologies, Clinical Characteristics and Outcomes of Hypoxic Hepatitis in Children - Phuc, Phan Huu; Anh, Nguyen Duc; Trinh, Nguyen Phuong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2DO - 10.25073/2588-1132/vnumps.4900, 2026)
Etiologies, Clinical Characteristics and Outcomes of Hypoxic Hepatitis in Children Objectives: This study aimed to describe etiologies, clinical profiles, and outcomes of hypoxic hepatitis (HH) in children admitted to the pediatric intensive care unit (PICU). Methods: A descriptive study was conducted on critically ill children admitted to the PICU of Vietnam National Children’s Hospital from November 2020 to July 2021. HH was defined as a ≥20-fold increase in serum alanine aminotransferase (ALT) and/or aspartate aminotransferase (AST) above the age-specific upper limit of normal, occurring in the context of impaired hepatic oxygen delivery and after exclusion of other causes of acute liver injury. Clinical features, laboratory findings, and outcomes were collected and summarized descriptively. The primary outcome was 28-day mortality. Results: Among 227 critically ill children, 22 cases (9.7%) were identified as HH. The most common underlying conditions included septic shock (63.6%), cardiogenic shock (27.3%), cardiac arrest (27.7%), and severe hypoxemia (18.2%). Serum AST and ALT levels increased rapidly, peaking within 24–48 hours after admission, followed by a gradual decline to near-normal levels within 9–11 days. The 28-day mortality rate in the HH group was 45.5%. Compared with children without HH, those with HH showed higher mortality and tended to require longer durations of mechanical ventilation and PICU stay. Conclusion: Hypoxic hepatitis is not uncommon among critically ill children and typically occurs in the setting of severe systemic illness. It may serve as a clinical indicator of disease severity and warrants early recognition in pediatric intensive care practice.